2015
DOI: 10.1103/physreva.92.023614
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional theory for the crystalline phases of a two-dimensional dipolar Fermi gas

Abstract: Density-functional theory is utilized to investigate the zero-temperature transition from a Fermi liquid to an inhomogeneous stripe, or Wigner crystal phase, predicted to occur in a one-component, spin-polarized, two-dimensional dipolar Fermi gas. Correlations are treated semi-exactly within the local-density approximation using an empirical fit to Quantum Monte Carlo data. We find that the inclusion of the nonlocal contribution to the Hartree-Fock energy is crucial for the onset of an instability to an inhomo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 28 publications
4
24
1
Order By: Relevance
“…With a self-consistent solution of the gap and number equations, we have compared the interlayer superfluidity in the unscreened case with the NS and the SS ones. We have observed that within our NS scheme the bilayer system becomes unstable towards the density wave instability at small layer spacings, in agreement with many similar studies [39][40][41]. But once the effects of interlayer pairing are included in the screening this instability goes away.…”
Section: Discussionsupporting
confidence: 91%
“…With a self-consistent solution of the gap and number equations, we have compared the interlayer superfluidity in the unscreened case with the NS and the SS ones. We have observed that within our NS scheme the bilayer system becomes unstable towards the density wave instability at small layer spacings, in agreement with many similar studies [39][40][41]. But once the effects of interlayer pairing are included in the screening this instability goes away.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore inhomogeneous density phases such as density waves or quantum droplets [31] would be naturally expected in this regime. Here, we should mention that the density-wave instability within different approximations has been also predicted for ultracold dipolar systems with anisotropic dipole-dipole interaction [32][33][34][35] as well as in layered dipolar structures [36][37][38]. However, its emergence in a single-layer system, with a purely isotropic dipole-dipole interaction has been the subject of much dispute [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…While the stripe or density-wave phase is naturally expected in an isolated two-dimensional (2D) system of tilted dipolar bosons [21,22] and fermions [23][24][25][26][27][28][29] due to the anisotropy of the dipole-dipole interaction, this instability has been the subject of much dispute in the limit of perpendicular dipoles, where the inter-particle interaction is isotropic. While mean-field approximation [23] as well as density-functional theory (DFT) [30] and Singwi-Tosi-Land-Sjölander (STLS) [25] calculations all predict stripe phase formation at relatively low interaction strength for 2D dipolar fermions, quantum Monte Carlo (QMC) simulations suggest that the stripe phase never becomes energetically favorable, up to the liquid-to-solid phase transition for perpendicular bosons [22] and fermions [31].…”
Section: Introductionmentioning
confidence: 99%